Effect of ionizing radiation on the colorimetric properties of PVA-GTA Xylenol Orange Fricke gel dosimeters. (March 2021) - Gallo, Salvatore; Pasquale, Stefania; Lenardi, Cristina; Veronese, Ivan; Gueli, Anna Maria
Abstract: Fricke gel dosimeters were prepared using a matrix based on poly(vinyl-alcohol) chemical cross-linked with glutaraldehyde and loaded with Xylenol Orange. The samples were irradiated with gamma rays to doses in the range of 5–30 Gy and the consequent color changes were investigated by using spectrophotometric and colorimetric techniques. Starting from the measurement of the transmittance spectra, an analysis of the color of the dosimeters was carried out considering the CIELAB color space. It allowed to highlight correlations between the color coordinates and the dose. Furthermore, the auto-oxidation processes occurring in the samples were studied by colorimetric measurements on both un-irradiated and irradiated samples at different times, up to two-week post-irradiation. The results showed no significant differences in the oxidation effect on the dosimeters, at least in the investigated dose interval. The study suggested that colorimetric analysis, combined with the spectrophotometric one, can be a useful tool for characterizing the samples in view of a standardization of Fricke gel dosimetry. Highlights: The color specification of the Fricke gels has been performed. L∗ and b∗ follow a decrescent exponential trend with increasing dose values. Reconstructed dose values are calculated at different times in 0–30 Gy range. Gels, measured at different times, oxide in an equal way with the considered dose-range.